2012
DOI: 10.3109/0886022x.2012.731999
|View full text |Cite
|
Sign up to set email alerts
|

The Biochemical and Histopathological Investigation of Amlodipine in Ethylene Glycol-Induced Urolithiasis Rat Model

Abstract: Background: Urinary calculi are a common and severe problem, which are formed by urolithiasis or by the formation of calcium oxalate (CaOx) crystals in the kidneys. Many treatment options such as drugs, various herbal preparations, surgical removal of the stones, and extracorporeal shock wave lithotripsy have been applied for this condition. The aim of this study is to assess the effects of the drug amlodipine in an experimentally induced urolithiasis rat model. Materials and methods: The effect of 5 mg/kg aml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…carota . EG and NH 4 Cl induced hyperoxaluria model of urolithiasis was selected for the study due to its simplicity, popularity [35] and the fact that it induces hyperoxaluria which is a crucial risk factor for CaOx urolithiasis in clinical setting [36] . Cystone was used as a standard control in the present study considering it is a polyherbal formulation which is extensively used for the treatment of urolithiasis in clinical practice [37] .…”
Section: Discussionmentioning
confidence: 99%
“…carota . EG and NH 4 Cl induced hyperoxaluria model of urolithiasis was selected for the study due to its simplicity, popularity [35] and the fact that it induces hyperoxaluria which is a crucial risk factor for CaOx urolithiasis in clinical setting [36] . Cystone was used as a standard control in the present study considering it is a polyherbal formulation which is extensively used for the treatment of urolithiasis in clinical practice [37] .…”
Section: Discussionmentioning
confidence: 99%
“…On the 59th day after the OVX, inflammation was induced in groups 2, 4, 5, and 6 by four separate subcutaneous injections of talc (magnesium silicate, 3.2 g in total per animal) in sterile saline in the back of the animals as previously described [23,24]. Groups 5 and 7 were administered AML 5 mg/kg orally [4] and groups 6 and 8 were administered LAC 4 mg/kg orally [25] from the 60th to the 80th day. Experimental design and all animal groups are shown in Fig.…”
Section: Experimental Groupsmentioning
confidence: 99%
“…Apart from the benefits of CCBs, studies have shown that it is an antioxidant in vessels in vitro [2]. Our previous studies and those of others demonstrated that amlodipine and lacidipine have anti-inflammatory and antioxidant effects [3,4]. This anti-inflammatory effect is considered to be based on over augmentation of nitric oxide production [5] and a reduction of oxidative stress [6].…”
Section: Introductionmentioning
confidence: 96%
“…In several studies, AML had protective effects in the liver (Dursun et al ., ) and other tissues (Halici et al ., ) of rats with I/R models. AML has also had effects on urolithiasis (Albayrak et al ., ), inflammation (Suleyman et al ., ) and osteoporosis (Halici et al ., ). When we consider this data, we see that the systemic application of AML has a positive effect on oxidant and antioxidant balance.…”
Section: Introductionmentioning
confidence: 99%